Exploring strain diversity of dominant human skin bacterial species using single-cell genome sequencing - Ide, Keigo; Saeki, Tatsuya; Arikawa, Koji; Yoda, Takuya; Endoh, Taruho; Matsuhashi, Ayumi; Takeyama, Haruko; Hosokawa, Masahito (Frontiers in Microbiology, 2022)
To understand the role of the skin commensal bacterial community in skin health and the spread of pathogens, it is crucial to identify genetic differences in the bacterial strains corresponding to human individuals. A culture-independent genomics approach is an effective tool for obtaining massive high-quality bacterial genome. Here we present a single-cell genome sequencing to obtain comprehensive whole-genome sequences of uncultured skin bacteria from skin swabs. We recovered 281 high-quality (HQ) and 244 medium-quality single-amplified genomes (SAGs) of multiple skin bacterial species from eight individuals, including cohabiting group. From the same skin swabs, single-cell sequencing outperformed in the genome recovery, showing 10-fold non-redundant strain genomes compared to the shotgun metagenomic sequencing and binning approach. We then focused on the abundant skin bacteria and identified intra-species diversity, especially in 47 Moraxella osloensis derived HQ SAGs, characterizing the strain-level heterogeneity at the level of mobile genetic element profiles, including plasmids and prophages. Even between the cohabiting individual hosts, they have unique skin bacterial strains in the same species, which shows microdiversity in each host. Genetic and functional differences between skin bacterial strains are predictive of in vivo competition to adapt bacterial genome to utilize the sparse nutrients available on the skin or produce molecules that inhibit the colonization of other microbes or alter their behavior. Thus, single-cell sequencing helps explore the skin commensal bacteria at the strain level, linking taxonomic and functional information with the aid of conventional isolate cultivation and metagenomic sequencing.